Enteroparasitismo y estado nutricional en escolares de institución educativa I.E. Nª38019 señor de los Milagros; Jesús Nazareno, Ayacucho, 2017 - Inga Muchari, Paola Giovanna (2019)
The present research work was carried out with the objective of determining the frequency of enteroparasites, nutritional status and relating enteroparasitism with nutritional status in schoolchildren of educational institution I.E. Nª38019 señor de los Milagros; Jesus Nazareno, Ayacucho. 2017; in the clinical analysis laboratory of the Jesús Nazareno Support Hospital. 2017; in the clinical analysis laboratory of the Jesús Nazareno Support Hospital. The sample consisted of 90 schoolchildren. The research design was non-experimental, the univariate and bivariate analyzes were carried out, considering a level of confidence at 95% and a significant value with a P value of less 0.05. The enteroparasite species most frequently is Giardia lamblia, being present in 52.4% of children (11), followed by Estrongyloides stercoralis and Trichuris trichiura with 19% (4) in both cases, while Ascaris lumbricoides only it is present in 9.5% (2) children. When performing the chi-square test, a significant association was found (p <0.05) between the presence of enteroparasitosis and the nutritional status of the children, that is, the presence of these organisms influences the nutritional status. It is observed that among the parasitized, those who have nutritional status of thinness are the most frequent, representing 81% (17 children) and only 19% (4 children) are considered normal. On the other hand, among the non-parasitized 62.3% (43 children) are normal.